Resilience in cogeneration systems: Metrics for evaluation and influence of design aspects - da Silva, Fellipe Sartori [UNESP]; Matelli, José Alexandre [UNESP] (Elsevier, 2021)
Energy systems are part of the critical infrastructures, and therefore any dysfunctionality can cause reactions in crucial societal fields. The growth of unexpected events is affecting these systems and exposing their vulnerability by leading them to abrupt disruptions. Resilience is a relatively recent concept in thermal engineering field that is receiving attention due to the consideration of these low-probability high-impact situations. This work aims to keep developing a previously proposed method for resilience evaluation in energy systems by considering system recovery and contributing with new metrics. Additionally, the influence of repairing actions in resilience is investigated. All the metrics converged to the same system as the most resilient one, proving the robustness and reliability of the method and the importance of redundancy to the system design, once it is the capital difference between the analyzed configurations. The addition of repairing actions enhanced resilience of all the systems, mostly the less resilient ones. The variation of input parameters revealed that operating time is an important key to resilience evaluation. It also indicated that increasing repair probability significantly improves the resilience of systems without redundancies, revealing that improving repair conditions can be as good to resilience as considering redundancies in system design.
Keywords: Cogeneration; Critical infrastructure; Energy systems; Resilience; System design